Analisis Pengembangan Keripik Studi Kasus : Istana Nabila Medan Helvetia, Kota Medan - Nasution, May Sarah; Hasibuan, Syahbudin; Salqaura, Siti Sabrina (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
This study analyzes the development strategy of Istana Nabila Chips SME in Medan using a qualitative case study approach. SMEs play a vital role in Indonesia's economy, yet face challenges such as limited Capital (72.8% rely on personal funds) and intense competition. The research aims to identify strengthening factors and barriers in developing traditional snack businesses in the Digital era. The research method includes in-depth interviews with the business owner and three key employees, field observations, and analysis of financial documents and Social media from January-February 2025. Data were analyzed thematically with triangulation for validation. Results reveal four main strengths: (1) unique traditional recipes with 78% customer loyalty due to distinctive taste, (2) creative packaging featuring Medan's cultural elements enhancing visual appeal, (3) Social Capital based on familial relationships improving employee retention, and (4) active Digital Marketing through Instagram and WhatsApp contributing 65% of sales. However, the business faces weaknesses in conventional management, limited distribution (70% local sales), and human resource constraints. Development opportunities include 25% growth in snack e-commerce, Sharia KUR program (5% interest), and collaborations with local influencers. Main threats comprise price competition with national brands, raw material price fluctuations (40% increase during rainy season), and changing Gen Z consumer preferences toward healthier products. The study concludes by emphasizing the importance of integrative strategies combining local strengths with Digital adaptation.